Multilevel Botulinum Toxin A (Abobotulinum Toxin A) Injections in Spastic Forms of Cerebral Palsy: Retrospective Analysis of 8 Russian Centers Experience - O. A. Klochkova; A. L. Kurenkov; K. M. Karimova; B. I. Bursagova; L. S. Namazova-Baranova; A. M. Mamedyarov; L. M. Kuzenkova; I. M. Tardova; I. V. Fal'kovskiy; O. G. Dontzov; M. A. Ryzhenkov; V. A. Zmanovskaya; et al. (Union of pediatricians of Russia, 2016)
Background: The contemporary application of Botulinum toxin A (BTA) in cerebral palsy (CP) implies multilevel injections both in on-label and off-label muscles. However, there is no single international opinion on the effective and safe dosages, target muscles, and intervals between the injections.Objective: Our aim was to analyze the Russian multicenter independent experience of single and repeated multilevel injections of Abobotulinum toxin А in patients with spastic forms of CP.Methods: 8 independent referral CP-centers (10 hospitals) in different regions of Russia. Authors evaluated intervals between the injections, dosages of the BTA for the whole procedure, for the body mass, for the each muscle, and functional segment of the extremities.Results: 1872 protocols of effective BTA injections (1-14 repeated injections) for 724 patients with spastic CP were included. The age of the patients was between 8 months to 17 years 4 months at the beginning of the treatment (with a mean of 3 years 10 months). Multilevel BTA injections were indicated for the majority (n = 634, 87.6%) of the patients in all the centers. The medians of the dosages for the first BTA injection were between 30-31 U/kg (500 U), the repeated injections doses up to 45 U/kg (1000 U) (in most centers). The median intervals between the repeated injections were 180-200 days in 484 (66.9%) patients and 140-180 days in 157 (24.7%) patients. In 2 centers, children with GMFCS IV-V were injected more often than others.Conclusion: Multilevel BTA injections were indicated for the most patients. The initial dose of Abobotulinum toxin A was 30-31 U/kg. The repeated injections dose could increase up to 40 U/kg. The repeated injections were done in 140-200 days after the previous injection.